Ultra-Broadly Tunable Light Sources Based on the Nonlinear Effects in Photonic Crystal Fibers - Zhang, Lei.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This thesis examines laser generation from the ultraviolet to the short edge of the mid-infrared band by exploiting the nonlinear effects in photonic crystal fibers (PCFs). Several different physical mechanisms are investigated by using homemade PCFs with elaborately customized dispersion profiles. A particular focus is on the development of fiber optical parametric amplifiers (FOPAs) and oscillators (FOPOs) based on the PCFs with a zero-dispersion wavelength of ca. 1.06 μm. In particular, several schemes are proposed for solving the key problems involved in the application of FOPOs. These oscillators can be made more convenient to use by optimizing the wavelength-tuning mechanisms, and made more energy-efficient with the help of specially designed cavity structures. Today's oscillators are more reliable, powerful and maneuverable than ever. This thesis provides a systematic road map in connection with the study of nonlinear wavelength generation in PCFs, from their fiber design and technical fabrication, to their physical mechanism and experimental investigation.
Introduction -- New wavelength generation based on PCF with two zero dispersion wavelengths (TZDW) -- PCF based optical parametric amplifier (OPA) -- Widely tunable optical parametric oscillator (OPO) based on PCF -- PCF based OPO with high energy conversion efficiency -- Conclusion.
Keywords: Telecommunication; Lasers; Optical materials; Microwaves, RF Engineering and Optical Communications; Laser; Optical Materials